Use of Warfarin or Direct Oral Anticoagulants and Risk of Prostate Cancer in PCBaSe: A Nationwide Case-Control Study - Parker, Jonathan; Crawley, Danielle; Garmo, Hans; Lindahl, Bertil; Styrke, Johan; Adolfsson, Jan; Lambe, Mats; Stattin, Pär; Van Hemelrijck, Mieke; Beckmann, Kerri (Frontiers in Oncology, 2020)
Existing literature examining warfarin’s association with prostate cancer (PCa) risk provides conflicting results, while the association with direct oral anticoagulants (DOACs) has not yet been studied. We investigated the association of warfarin and DOAC use on PCa risk among men within the population-based Prostate Cancer database Sweden (PCBaSe), using a case-control design. The study population included PCa cases diagnosed 2014 - 2016 and five age-matched PCa-free controls. Conditional logistic regression was used to estimate odds ratios (ORs) with 95% confidence intervals (CI) for PCa associated with warfarin and DOAC use, adjusted for marital status, education level, other drug use, and comorbidities. Among 31,591 cases and 156,802 controls, there were 18,522 (9.8%) warfarin and 4,455 (2.4%) DOAC users. Warfarin ever-use was associated with reduced risk of PCa overall (OR 0.92 95% CI 0.88-0.96) as were both past and current use. DOAC use was not associated with PCa risk. For some warfarin exposures, decreased risk was observed for unfavourable PCa (high risk/locally advanced/distant metastatic) but not with favourable PCa (low/intermediate risk). Increased risk of favourable PCa was observed for men whose initial warfarin exposure occurred in the 12 month period before diagnosis (OR 1.39; 95% CI 1.13-1.70). Our findings are consistent with previous publications reporting decreased PCa risk with warfarin exposure. Increased risk of favourable PCa suggests detection bias due to increased prostate specific antigen testing when starting on warfarin. Decreased overall PCa risk could reflect bias due to reduced biopsy rates among long-term warfarin users.